Managing Asian Destinations (Perspectives on Asian Tourism,, 2018)
This book focuses on the planning, marketing, and management of Asian tourism destinations, and evaluates current developments within Southeast-Asia and the wider Asia-Pacific region. As more Asian destinations enter the global tourism arena and more Asian travellers look to explore destinations in Asia and beyond, an understanding of how Asian destinations practice tourism is crucial to the future sustainable development of global tourism. This book provides an invaluable stock of research and knowledge based on the Asian practice and experience in destination planning, marketing, and management, offering insights into the latest development and trends in the region.